A case report of fetal spinal meningomyelocella - Ana Kocevska; Bashkim Ismaili; Kristina Skeparovska; Dimitar Georgiev; Shenol Tahir; Aleksandar Nakov (My University, 2022)
Neural tube defects are congenital malformations of the CNS resulting from defective closure of the neural tube during early embryogenesis between 3rd and 4th week of intrauterine life. It involves defect in the skull, vertebral column, the spinal cord and other portion of CNS. It occurs about 1 to 5 per 1000 live births. Myelomeningocele is most common and severe form of spina bifida cystica, characterised by protrusion of spinal cord through the open vertebrae into the amniotic fluid. We present a case of a 25-year-old pregnant woman who came into our hospital in the 17th week of pregnancy with characteristic ultrasound signs for the presence of fetal spina bifida. Lumbosacral meningomyelocella was present. The anterior part of the head started to develop ‘‘the lemon sign’’ and cerebellum showed ‘‘the banana sign’’. Dilated lateral ventricle was also present. There was anamnesis for folic acid supplementation starting at 6 weeks of gestation. We performed induction of labour with oxytocine and termination of this pregnancy. The autopsy report showed the presence of spina bifida in the lumbosacral region, with a defect of the skin and the vertebral arches, measuring 1.7 × 1 cm, with protrusion of meninges and the spinal cord.
Abstracts of the 32nd World Congress on Ultrasound in Obstetrics and Gynecology, 16–18 September 2022, London, UK & Virtual